Types of Facets on the Superior Articular Surface of Isan-Thai Dried Calcanei - Iamsaard,Sitthichai (Sociedad Chilena de Anatomía, 2015)
The patterns of talar articulating facets must be concerned in surgical procedure or the internal and external fixation in various diseases of the foot. The variant types of calcaneal facets on the superior articular surface have been reported in many races except in Thais. This study therefore was aimed to investigate the patterns of superior articulating facet of dried calcanei in Isan-Thais. The identified 396 Isan- Thai dried calcanei (202 males and 194 females) were carried out for variant superior facet observations. The results showed that types of facets observed could be classified into three major types (Type 1 [60.86%], Type 2 [38.64%], and Type 4 [0.51%], respectively). In sub-type classifications, there were Type 1A (24.75%), Type 1B (36.11%), Type 2A (12.88%), Type 2B (14.14%), Type 2C (2.78%), Type 2D (8.84%), and Type 4 (0.51%), respectively. Additionally, it was found that the percentage of Type 2A of male (15.84%) was much greater than that of female (9.79%) compared to those of other types. This incidence of facet types is valuable information for Thai orthologists to concern about treating in talocalcaneal joint area.